Crystal Engineering of Schiff Base Zn(II) and Cd(II) Homo- and Zn(II)M(II) (M = Mn or Cd) Heterometallic Coordination Polymers and Their Ability to Accommodate Solvent Guest Molecules - Olga Danilescu; Paulina N. Bourosh; Oleg Petuhov; Olga V. Kulikova; Ion Bulhac; Yurii M. Chumakov; Lilia Croitor (Molecules, 2021)
Based on solvothermal synthesis, self-assembly of the heptadentate 2,6-diacetylpyridine bis(nicotinoylhydrazone) Schiff base ligand (H2L) and Zn(II) and/or Cd(II) salts has led to the formation of three homometallic [CdL]n (1), {[CdL]∙0.5dmf∙H2O}n (2) and {[ZnL]∙0.5dmf∙1.5H2O}n (3), as well as two heterometallic {[Zn0.75Cd1.25L2]∙dmf∙0.5H2O}n (4) and {[MnZnL2]∙dmf∙3H2O}n coordination polymers. Compound 1 represents a 1D chain, whereas 2–5 are isostructural and isomorphous two-dimensional structures. The entire series was characterized by IR spectroscopy, thermogravimetric analysis, single-crystal X-ray diffraction and emission measurements. 2D coordination polymers accommodate water and dmf molecules in their cage-shaped interlayer spaces, which are released when the samples are heated. Thus, three solvated crystals were degassed at two temperatures and their photoluminescent and adsorption–desorption properties were recorded in order to validate this assumption. Solvent-free samples reveal an increase in volume pore, adsorption specific surface area and photoluminescence with regard to synthesized crystals.